Deciphering the Interconnection of Good Governance, Rule of Law, and Economic Development in Pakistan: A Critical Evaluation - Saleem, Abdul Rehman; Din, Shah Jalal ud; Ullah, Zia; Irshad, Samra (Law and Policy Review, 2023)
The good governance concept was borrowed by International Financial Institutions (IFIs) to bring transparency and rule of law in developing countries for the purpose of development. The IFIs stress upon the countenance of good governance, however, the factors including elite mandated corruption, lack of transparency, and disregard to rule of law has made Pakistan unable to achieve development. The current study has attempted to examine the intricate relationship between good governance, rule of law, and economic development in Pakistan with scrutinizing the impediments that thwart their efficacious execution. Through a developmental lens, this inquiry has scrutinized the socio-legal context of Pakistan and pinpointed the key hurdles to render the countenance of good governance. By examining the pertinent literature and data, the current study has illuminated the ramifications of these obstacles for the economic development of the country. The research findings have underscored the urgency of addressing issues, such as inadequate governance, lack of transparency, corruption, and non-adherence to rule of law. The study is culminated by underscoring the significance of promoting transparency, accountability, and pro-people policies to foster sustainable economic growth to advance development outcomes in Pakistan. Moreover, it has rendered a critical evaluation of instances into three accounts; the first account explicates the conception of good governance elaborated by IFIs and second account elaborates the argument of state functionaries in avoiding good governance and rule of law with resultant effects on development. The third account finally extrapolates the conclusion with serious recommendations.